Gender in the World Food Economy: Inequitable Transformation of Haiti’s Food Economy - Vansteenkiste, Jennifer (Frontiers in Communication, 2022)
Over the past five decades, agricultural trade liberalization and integration into the global food system have undermined gender equality, women's empowerment, and food security in Haiti. International actors who design agricultural policies are aware of gendered contributions to Haitian food security, yet ignore their knowledge to privilege an ideological belief that trade liberalization and structural adjustment programs will advance gender equality. I argue that agriculture and food policies must treat gender roles and responsibilities as constitutive to the solution by recognizing their critical contribution to the structure of Haitian agrarian society and accordingly food security. I advance this claim by analyzing scholarly literature, institutional documents, and interviews with interlocutors (n=292) from rural, peri-urban, and urban settings across Haiti to document how: (a) dominant narratives support an ideological belief that trade liberalization will advance gender equality; (b) the integration of Haiti’s local food economy into the world food economy demands the reorientation of gendered labour; (c) women must participate in a system that while purporting to improve food security, ultimately diminishes their nutrition and social, economic and political wellbeing. This research documents that policies designed to globalize Haiti’s food economy on the premise of improving food security actually force women to abandon agricultural production and intensify their labour in less lucrative distribution and consumption roles of imported goods. This analysis documents that the transition ultimately reifies gender inequalities, heighten food insecurity, and contributes to feminist food scholarship.